MULTICULTURAL EDUCATION IN SALAF PESANTREN AND PREVENTION OF RELIGIOUS RADICALISM IN INDONESIA - Marzuki Marzuki; Miftahuddin Miftahuddin; Mukhamad Murdiono (Jurnal Cakrawala Pendidikan, 2020)
Islamic boarding school (pesantren) is the oldest Islamic educational institution in Indonesia. Pesantren is recognized as one of the institutions that can encourage the realization of multiculturalism amongst Muslims. However, recently pesantren has been alleged to be one of the centers for the spread of religious radicalism. This study is aimed at analyzing multicultural education in salaf (traditional) pesantren, that is appropriate and be able to prevent the growth and development of religious radicalism in Indonesia. The study is a qualitative research with a phenomenological approach involving four salaf pesantrens in Java; namely Al-Qadir Pesantren of Sleman Yogyakarta, Dar al-Tauhid of Cirebon, Roudlatuth Thalibin of Rembang, and Tebuireng of Jombang. The research data were collected by observation, interviews, documentation, and focus-group discussions (FGD). Data were analyzed using an interactive technique. Findings showed that the forms of multicultural education at the four salaf pesantrens generally have similarities in the application of multiculturalism core values. However, each pesantren has its own specific peculiarities. The various cultures built up by the four caregivers of the salaf pesantrens have been effective to prevent the growth and development of religious radicalism at the  pesantren, particularly, and in the society, more generally.